Aspectos epidemiológicos, transmissão e manejo da antracnose do feijão fava - Gomes, Rommel dos Santos Siqueira (2019)
The lima beans (Phaseolus lunatus L.) is the second most important legumes in the genre. One of the problems that affect the crop is anthracnose, one of the main diseases, often found in production fields, causing a reduction in crop productivity. The objective of the research was to study epidemiological aspects and to verify the transmission of Colletotrichum truncatum via seeds and the management of anthracnose of lima beans with resistance inducers under field conditions. In the first experiment, it was evaluate the temporal progress of anthracnose of lima beans from the severity, incidence, disease index and area under the disease progress curve (AUDPC) under field conditions, and the lima bean productivity. The experimental design was a randomized block (DCB) with nine treatments, represented by the traditional varieties of lima beans (UFPB02, UFPB 04 UFPB 05 UFPB06, UFPB11, UFPB13, UFPB14, UFPB19 and UFPB20) and subplots was evaluated influence of 7, 14, 21, 28 and 35 days of evaluation for the severity and incidence of the disease, at 2015 and 2017, with four repetitions. In the second experiment, it was compared methods of inoculation and exposure times of lima bean seeds to C. trucatum, evaluating the severity of anthracnose on stems, seedlings, disease index, AUDPC, transmission rate, symptoms of percentage in leaves, stems and tipping and physiological variables such as seedling height, shoot dry weight, root and total and hard and dead seeds percentage. It was used completely randomized factorial 4 x 5, with five repetitions, the methods of inoculation by direct contact the mycelium (1) direct contact with a water mannitol restrictor (2) direct contact with a water sucrose restrictor (3) and immersion in conidia suspension (4) and exposure times of 0, 36, 60, 84 and 108 h per method. In the third experiment, it was determined the effects of different resistance inducers on the control of C. truncatum in lima bean plants, in two cultivation regions. Also using DBC, with fourteen treatments, six of which are resistance inducers, phosphorylated mannooligosaccharide (MOF), acibenzolar-S-methyl (SM), citrus biomass (BC), K phosphite (FK), silicate clay (AS) and Ca and Mg silicate (SCM), on two types of association, with and without carbendazim (CA) fungicide, plus the control with fungicide CA and the control, with four replications and, in thesubplots, the influence of the regions (Areia and Lagoa Cultivation). For the first experiment, it was possible to verify that there was an interaction between varieties and crop years, generating favorable and not favorable environments for the incidence of anthracnose, being possible to observe the behavior of the varieties in the years 2015 and 2017. It was also observed genetic variability between the creole varieties of lima beans for resistance to C. truncatum, where the varieties UFPB04 and UFPB20 were considered more resistant to the pathogen, with the ability to be used in genetic improvement programs for lima beans. For the results of the second experiment, the method of inoculation by direct contact with the water restrictor mannitol for 36 h was the most suitable for inoculation of C. truncatum in lima bean seeds, since it provided a higher incidence of infected seedlings without interfering in the parameters physiological. However, the damage caused by C. truncatum on the performance of lima bean seeds, increases with increasing exposure time, regardless of the inoculation method. Based on the results of the third experiment, the ASM, BC, FK, AS and SCM inducers with or without the fungicide CA showed the greatest potential to reduce anthracnose caused by C. truncatum in broad bean plants, showing the lowest values for the area below the disease progress curve and disease index over the evaluation period. The progression of the disease provided a change in enzyme activity, where ASM, BC, FK, AS and SCM inducers with or without the fungicide CA promoted the highest enzymatic activities and gas exchange rates compared to the other inducers. The use of biotic resistance (BC) and abiotic resistance (ASM, FK, AS and SCM) showed a high potential for combating anthracnose in lima bean plants, however, the mechanisms of action differ between the different inductors, when combined with the fungicide and between the different growing regions.